Racial Discrimination in Employment in Canada - Andiappan, P.; Crestohl, Mark; Singh, Jang (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The purpose of this study is to examine recent developments in the legal remedies for racial discrimination in employment in Canada.